An integrative geochronological framework for the Pleistocene So'a basin (Flores, Indonesia), and its implications for faunal turnover and hominin arrival. (15th October 2022) - van den Bergh, Gerrit D.; Alloway, Brent V.; Storey, Michael; Setiawan, Ruly; Yurnaldi, Dida; Kurniawan, Iwan; Moore, Mark W.; Jatmiko,; Brumm, Adam; Flude, Stephanie; Sutikna, Thomas; Setiyabudi, Erick; et al.
Abstract: Flores represents a unique insular environment with an extensive record of Pleistocene fossil remains and stone artefacts. In the So'a Basin of central Flores these include endemic Stegodon, Komodo dragons, giant tortoises, rats, birds and hominins, and lithic artefacts that can be traced back to at least one million years ago (1 Ma). This comprehensive review presents important new data regarding the dating and faunal sequence of the So'a Basin, including the site of Mata Menge where Homo floresiensis -like fossils dating to approximately 0.7 Ma were discovered in 2014. By chemical fingerprinting key silicic tephra originating from local and distal eruptive sources we have now established basin-wide tephrostratigraphic correlations, and, together with new numerical ages, present an update of the chronostratigraphy of the So'a Basin, with major implications for the faunal sequence. These results show that a giant tortoise and the diminutive proboscidean Stegodon sondaari last occurred at the site of Tangi Talo ∼1.3 Ma, and not 0.9 Ma as previously thought. We also present new data suggesting that the disappearance of giant tortoise and S. sondaari from the sedimentary record occurred before, and/or was coincident with, the earliest hominin arrival, as evidenced by the first records of lithic artefacts occurring directly below the 1 Ma Wolo Sege Tephra. Artefacts become common in the younger layers, associated with a distinct fauna characterized by the medium-sized Stegodon florensis and giant rat Hooijeromys nusatenggara . Furthermore, we describe a newly discovered terrace fill, which extends the faunal record of Stegodon in the So'a Basin to the Late Pleistocene. Our evidence also suggests that the paleoenvironment of the So'a Basin became drier around the time of the observed faunal transition and arrival of hominins on the island, which could be related to an astronomically-forced climate response at the onset of the Mid-Pleistocene Transition (MPT; ∼1.25 Ma) leading to increased aridity and monsoonal intensity. Highlights: The ancestral population of Homo floresiensis probably arrived on Flores after 1.3 Ma but certainly before 1 Ma. The oldest megafauna on Flores, including Komodo dragon, diminutive Stegodon and giant tortoise, was present on Flores by 1.4 Ma. A fauna turnover coincided with the Mid-Pleistocene Transition and a shift from a forested to a grassland dominated biotope in the So'a Basin. Despite major volcanic eruptions and climate oscillations a stable fauna appears to have persisted until the arrival of humans at 46 ka. Chemical fingerprinting of distal tephra layers in the So'a Basin has the potential for regional tephrostratigraphic correlations.